Detection of inducible clindamycin resistance and susceptibilities to other antimicrobial agents in clinical isolates of Staphylococcus aureus - Toleti, Sunita; Bobbillapati, Janaki Ram; Kollipaka, Sree Ramarao; Myneni, Ramesh Babu (International Journal of Research in Medical Sciences, 2017)
Background: The resistance to antimicrobial agents among staphylococci is an increasing problem. Clindamycin is commonly used for the treatment of skin and soft tissue infections produced by Staphylococcus aureus and its widespread use has led to its resistance by different mechanisms & hence it is important to detect this. In vitro, routine tests may fail to detect inducible clindamycin resistance due to erm genes resulting in treatment failure, thus necessitating the need to detect such resistance by a simple D-test on a routine basis. Objective: To find out the percentage of inducible clindamycin resistance in our hospital using D-test and their susceptibilities to other antimicrobial agents to guide therapy. Methods: One hundred and two S. aureus isolates from various clinical samples were evaluated and methicillin resistance was determined using cefoxitin (30 mcg) disc and inducible resistance to clindamycin was detected by D-test as per CLSI guidelines. Antibiotic susceptibility to other antimicrobial agents was done by Kirby Bauer’s disc diffusion method. Results: Nineteen (18%) isolates showed inducible clindamycin resistance, 12 (11%) showed constitutive resistance and 22 (21%) showed MS phenotype. All the three resistance patterns were higher in Methicillin Resistant Staphylococcus aureus (MRSA) as compared to Methicillin Sensitive Staphylococcus aureus (MSSA). Conclusion: Our study showed, that D-test should be used as a mandatory method in routine disc diffusion testing to detect inducible clindamycin resistance for optimum treatment of patients.